Metabarcoding of canopy arthropods reveals negative impacts of forestry insecticides on community structure across multiple taxa. Issue 4 (30th January 2022) - Leroy, Benjamin M. L.; Seibold, Sebastian; Morinière, Jérôme; Bozicevic, Vedran; Jaworek, Jessica; Roth, Nicolas; Vogel, Sebastian; Zytynska, Sharon; Petercord, Ralf; Eichel, Peter; Weisser, Wolfgang W.
Abstract: Insecticides used to combat outbreaks of forest defoliators can adversely affect non‐target arthropods. Forestry insecticides typically suppress Lepidoptera larvae which are the cornerstone of the canopy community of deciduous oak forests. The abrupt removal of this dominant component of the food web could have far‐reaching implications for forest ecosystems, yet it is rarely investigated in practice owing to several methodological shortcomings. The taxonomic impediment and the biased nature of arthropod sampling techniques particularly impede the assessment of insecticide impacts on diverse communities. To tackle this issue, we propose an experimental approach combining sampling by pyrethrum knockdown and species determination via DNA metabarcoding, using community subsampling to derive estimates of species abundances. We applied this protocol to investigate the short‐term effects of the insecticides diflubenzuron (DFB) and Bacillus thuringiensis var. kurstaki (BTK) on canopy‐dwelling arthropod communities in German oak woodlands. Our approach allowed us to detect most of the diversity and integrate species abundances in our analyses. By classifying arthropod species into assemblages based on their expected sensitivity rather than coarse taxonomic groupings, we could unveil substantial effects of DFB across multiple taxa 5 weeks after application. Although strong effects on single species appear related to direct toxicity, substantial impacts of DFB on parasitoids and xylophagous beetles suggest that anti‐defoliator treatments can have previously unsuspected indirect effects on some components of forest arthropod communities. The impacts of BTK on community structure were consistent with that of DFB though much weaker. Synthesis and applications . Comparing diversity patterns in the arthropod communities of sprayed and unsprayed oak canopies, our results show that selective insecticides can alter species diversity in presumably non‐sensitive taxa. Even though the ecological significance of these impacts has yet to be assessed in an operational setting, their existence calls for increased regulatory scrutiny on indirect effects. As community approaches become more attainable with the rapid development of DNA metabarcoding, we suggest the inclusion of community‐level end points as regulatory requirements for the approval of forest‐use insecticides. Abstract : Comparing diversity patterns in the arthropod communities of sprayed and unsprayed oak canopies, our results show that selective insecticides can alter species diversity in presumably non‐sensitive taxa. Even though the ecological significance of these impacts has yet to be assessed in an operational setting, their existence calls for increased regulatory scrutiny on indirect effects. As community approaches become more attainable with the rapid development of DNA metabarcoding, we suggest the inclusion of community‐level end points as regulatory requirements for the approval of forest‐use insecticides. Zusammenfassung: Insektizide, die zur Bekämpfung von Schädlingsausbrüchen in Wäldern eingesetzt werden, können sich negativ auf Nichtziel‐Arthropoden auswirken. Insektizide für den Forstbereich richten sich in der Regel gegen Lepidoptera‐Larven, die einen bedeutenden Teil der Lebensgemeinschaften in den Baumkronen von Eichenwäldern darstellen. Der abrupte Wegfall dieser Gruppe als Bestandteil des Nahrungsnetzes könnte weitreichende Folgen für Waldökosysteme haben, wird aber in der Praxis aufgrund von mehreren methodischen Schwierigkeiten nur selten untersucht. Insbesondere das sogenannte "taxonomic impediment" sowie Verzerrungen durch die gängigen Probenahmenverfahren für Arthropoden erschweren die Bewertung der Effekte von Insektiziden auf die Waldlebensgemeinschaften. Zur Lösung dieses Problems schlagen wir einen experimentellen Ansatz vor, der Pyrethrum‐Knockdown‐Sampling und taxonomische Bestimmung mittels DNA‐Metabarcoding kombiniert. Mit Hilfe von Teilproben kann eine Schätzung der dazugehörigen Abundanzen vorgenommen werden. Diese Methoden wurden angewendet, um die kurzfristigen Auswirkungen der Insektizide Diflubenzuron (DFB) und Bacillus thuringiensis var. kurstaki (BTK) auf die Arthropoden‐Lebensgemeinschaften in den Baumkronen von Eichenwäldern in Deutschland zu untersuchen. Mit diesem Ansatz war es möglich, den Großteil der nachgewiesenen Arten sowie deren Abundanzen in die Analysen einfließen zu lassen. Durch die Einteilung von Arthropodenarten basierend auf ihrer erwarteten Sensitivität anstelle von groben taxonomischen Klassifizierungen konnten wir in fünf Wochen nach der Insektizidanwendung erhobenen Daten erhebliche Auswirkungen von DFB auf mehrere Taxa nachweisen. Auch wenn starke Effekte auf einzelne Arten wahrscheinlich auf direkte Toxizität zurückzuführen sind, deuten die erheblichen Auswirkungen von DFB auf Parasitoide und auf xylophage Käfer darauf hin, dass Pestizideinsätze gegen folivore Insekten in Wäldern auch bisher unbekannte indirekte Effekte auf einige Teile der Arthropodengemeinschaften haben können. Die Auswirkungen von BTK auf die Struktur dieser Lebensgemeinschaften entsprachen denen von DFB, waren aber viel schwächer ausgeprägt. Synthese und Anwendung . Der Vergleich der Diversitätsmuster in den Arthropodengemeinschaften von behandelten und unbehandelten Eichenwäldern zeigt, dass selektive Insektizide die Artenvielfalt von vermeintlich nicht betroffenen Taxa beeinflussen können. Auch wenn die ökologische Bedeutung dieser Auswirkungen für die Praxis noch bewertet werden muss, ist eine genauere Untersuchung und Berücksichtigung der indirekten Effekte erforderlich. Da DNA‐Metabarcoding zunehmend Analysen auf Gemeinschaftsebene ermöglicht, schlagen wir vor, Endpunkte auf Gemeinschaftsebene in Zulassungsprozessen für Insektizide im forstlichen Bereich zu berücksichtigen.